PENGARUH LAYANAN INFORMASI KARIR TERHADAP PILIHAN KARIR PADA PESERTA DIDIK KELAS XII SMA IMMANUEL PONTIANAK - Suhardi, Sonia; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractOn this research we know how to effect of career information service about choosing career after high school graduating on student class 12 Immanuel Senior High School, West Borneo. The purpose of this research is about to  description the effect of career information service about choosing career after high school. The method of this research is description method with quantitative approachment, that the procedure can solve the problem with showing the effect of the career information service. Sample of this research are 50 respondent’s class 12. The way of collecting data is un-direct communication technique, with collecting data instrument is questionnaire. .analyst data technique is presentation formula, analyst product moment, and continuing by determination coefficient. Depends on the analyst data result indicate that the career information that explained by the teacher to student class 12 reach score to 74,40 percent, that reached at position on  the good  range. Meanwhile, the result of choosing career after graduating senior high school reach score 56,15 percent, this reached at position on the under standard range. The result of this research from  product moment analyst from two variable are 0,137 on rhitung, that means there was no relate between career information service and choosing career after graduating senior high school at student class 12 Immanuel senior high school, West Kalimantan. The big-small effect result of this research can be seeing by determination coefficient that can be found by Kd= 1,8 percent that means career information service that give by counseling teacher do not give effect to student choosing career on class 12 Immanuel senior high school, West Kalimantan. Keywords: Career Information Services, Choosing Career.